2008
DOI: 10.1074/jbc.m802300200
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Deletion of the Adenovirus-associated RNAI Terminal Stem Reveals a Surprisingly Active RNA Inhibitor of Double-stranded RNA-activated Protein Kinase

Abstract: Adenoviruses use the short noncoding RNA transcript virusassociated (VA) RNA I to counteract two critical elements of the host cell defense system, innate cellular immunity and RNA interference, mediated by the double-stranded RNA-activated protein kinase (PKR) and Dicer/RNA-induced silencing complex, respectively. We progressively shortened the VA RNA I terminal stem to examine its necessity for inhibition of PKR. Each deletion, up to 15 bp into the terminal stem, resulted in a cumulative decrease in PKR inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
74
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(80 citation statements)
references
References 46 publications
6
74
0
Order By: Relevance
“…*P < 0.01. 2α via dsRNA-induced protein kinase R activation (19)(20)(21). However, the roles played by VA-RNAs in the Ad vector-induced innate immune response have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…*P < 0.01. 2α via dsRNA-induced protein kinase R activation (19)(20)(21). However, the roles played by VA-RNAs in the Ad vector-induced innate immune response have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…VA-RNAs are synthesized by RNA polymerase III, are ≈160 nucleotides long, and are structurally highly conserved. Previous studies have demonstrated that VARNAs induce the phosphorylation of eukaryotic initiation factor-2α via dsRNA-induced protein kinase R activation (19)(20)(21).…”
mentioning
confidence: 99%
“…1A, nucleotides in outline font) (11,12,21). We have shown that the stability of the central domain structure is also highly sensitive to solution pH, suggesting the involvement of a protonated base-base tertiary interaction (8). Finally, Mg 2ϩ and PKR have been shown to induce similar structural rearrangements in the central domain (14), and Mg 2ϩ appears to fine-tune the mode and affinity of the PKR-VA RNA I interaction (22).…”
mentioning
confidence: 96%
“…Specific regulation of host genes by VA RNA Iderived microRNAs has been proposed (5,6), but a precise functional role in adenoviral replication has not yet been established (7). The remaining portion of the Dicer-processed VA RNA I is a truncated form of the transcript, lacking the viral microRNA sequences at both the 5Ј and 3Ј ends, that retains full activity against PKR (8). Paradoxically, full-length VA RNA I activates a second protein of the innate immune response, 2Ј-5Ј-oligoadenylate synthetase 1 (OAS1), leading to downstream activation of RNaseL and degradation of viral and cellular RNAs (9).…”
mentioning
confidence: 99%
“…Elucidating the mechanism by which PKR function is subverted by viral products has enhanced our understanding of how PKR and other eIF2α family kinases naturally function. In particular, viral mimicry appeared as a recurring theme: analysis of the pseudosubstrate inhibitor K3L from vaccinia virus revealed key molecular determinants required for PKR recognition of its natural substrate eIF2α (10)(11)(12); analysis of the RNA binding protein E3L from vaccinia virus revealed how PKR itself senses dsRNA through comparable infrastructure (13)(14)(15); and analysis of the RNA inhibitor VAI from adenovirus showed how a structured RNA decoy can competitively engage the dsRNA-binding domains of PKR in a manner that circumvents kinase domain activation (16)(17)(18).…”
Section: Significancementioning
confidence: 99%